Interparental Aggression and Children’s Adrenocortical Reactivity: Testing an Evolutionary Model of Allostatic Load - Davies, Patrick T. (2011)
Guided by an evolutionary model of allostatic load (Korte, Koolhaas, Wingfield, & McEwen, 2005), this study examined the hypothesis that the association between interparental aggression and subsequent changes in children’s cortisol reactivity to interparental conflict is moderated by their temperamental dispositions. Participants of the multi-method, longitudinal study included 201 two-year-old toddlers and their mothers. These children experienced elevated levels of aggression between parents. Consistent with the theory, the results indicated that interparental aggression predicted greater cortisol reactivity over a one year period for children who exhibited high levels of temperamental inhibition and vigilance. Conversely, for children with bold, aggressive temperamental characteristics, interparental aggression was marginally associated with diminished cortisol reactivity. Further underscoring its implications for allostatic load, increasing cortisol reactivity over the one year span was related to concomitant increases in internalizing symptoms but decreases in attention and hyperactivity difficulties. In supporting the evolutionary conceptualization, these results further supported the relative developmental advantages and costs associated with escalating and dampened cortisol reactivity to interparental conflict.